Functional Analysis of Nuclear Factor Y in the Wing-Dimorphic Brown Planthopper, Nilaparvata lugens (Hemiptera: Delphacidae) - Chen, Hao-Hao; Liu, Yi-Lai; Liu, Xin-Yang; Zhang, Jin-Li; Xu, Hai-Jun (Frontiers in Genetics, 2020)
Nuclear factor Y (NF-Y) is a heterotrimeric transcription factor with the ability to bind to a CCAAT box in nearly all eukaryotes. However, the function of NF-Y in the life-history traits of insects is unclear. Here, we identified three NF-Y subunits, NlNF-YA, NlNF-YB, and NlNF-YC, in the wing-dimorphic brown planthopper (BPH), Nilaparvata lugens. Spatio-temporal analysis indicated that NlNF-YA, NlNF-YB, and NlNF-YC distributed extensively in various body parts of fourth-instar nymphs, and were highly expressed at the egg stage. RNA interference (RNAi)-mediated silencing showed that knockdown of NlNF-YA, NlNF-YB, or NlNF-YC in third-instar nymphs significantly extended the fifth-instar duration, and decreased nymph-adult molting rate. The addition of 20-hydroxyecdysone could specifically rescue the defect in adult molting caused by NlNF-YARNAi, indicating that NlNF-Y might modulate the ecdysone signaling pathway in the BPH. In addition, NlNF-YARNAi, NlNF-YBRNAi, or NlNF-YCRNAi led to small and moderately malformed forewings and hindwings, and impaired the normal assembly of indirect flight muscles. Adult BPHs treated with NlNF-YARNAi, NlNF-YBRNAi, or NlNF-YCRNAi produced fewer eggs, and eggs laid by these BPHs had arrested embryogenesis. These findings deepen our understanding of NF-Y function in hemipteran insects.